The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1007/bf02123765
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to ATLV/HTLV-1 in Africa

Abstract: Almost 4000 sera from seven African states were examined for antibodies to ATLV/HTLV-1. Between 1% and 8% of healthy people from sub-Saharan Africa have such antibodies. The highest frequency was observed in Gabon. There were considerable variations between villages. The percentage of seropositives and the mean titre increased with age. Our findings suggest that the African continent is the largest endemic area for ATLV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 9 publications
1
15
0
1
Order By: Relevance
“…Moreover, Fleming et al (1983) reported that lymphoma patients with anti-HTLV antibodies existed in Nigeria. Hunsmann et al (1984) extended these studies and showed that 1 to 69o of the population of several African countries, Senegal, Liberia, Nigeria, Kenya, Gabon, Zaire and South Africa, were infected with HTLV.…”
Section: Atl and Anti-htl V Antibodies Outside Japanmentioning
confidence: 83%
“…Moreover, Fleming et al (1983) reported that lymphoma patients with anti-HTLV antibodies existed in Nigeria. Hunsmann et al (1984) extended these studies and showed that 1 to 69o of the population of several African countries, Senegal, Liberia, Nigeria, Kenya, Gabon, Zaire and South Africa, were infected with HTLV.…”
Section: Atl and Anti-htl V Antibodies Outside Japanmentioning
confidence: 83%
“…These retroviruses are found in foci of micro-endemicity, particularly in southern Japan,7 equatorial Africa,8,9 and parts of the Americas, including the Caribbean basin,10 and the Southeastern US 10. The frequency of antibodies in symptom-free adults throughout Sub-Saharan Africa has been reported to be from 3%–4% 11,12…”
Section: Introductionmentioning
confidence: 99%
“…For instance, South Africa has a prevalence of 0%,27,28 Zimbabwe 0.11%,29 Senegal 1.2%,30 Namibia 1%,31 Mozambique 0.7%,20,32 and Congo 0.7% 20,33. In Europe, it ranges from 0% to 0.02% 7,10.…”
Section: Discussionmentioning
confidence: 99%